The Iron Giant - Hughes, Ted (Faber and Faber Ltd, 1999)
A mysterious creature stalks the land, eating barbed wire and devouring tractors and plows. The farmers are mystified - and afraid. And then they glimpse him in the night: the Iron Giant, taller than a house, with glowing headlight eyes and an insatiable taste for metal. Where has he come from? Nobody knows. How was he made? Nobody knows. What they do know is that the Iron Giant must be stopped. But the real threat hovers above, darkening the sky with its scaly wings: a space-bat as big as Australia, hungry for every living thing it sees. And suddenly, the world needs a hero - a giant hero - like never before...
Keywords: Juvenile literature-Iron Giant (Fictitious character)-Motion picture books-Fiction